Outcomes of low-dose infliximab as an adjunctive therapy in patients with severe central nervous system tuberculosis - Dr Selwyn Selvakumar; Dr Nishi Somarkutty; Dr Jayavelu Hariram Prasad; Dr Priyanka Gautam; Dr Prabhakar Thirumal Appaswamy; Dr Naveen Cherian Thomas; Dr Joy Sarojini Michael; Dr Rajiv Karthik; Dr George M Varghese; Dr Abi Manesh (International Journal of Infectious Diseases)
Introduction: High-dose (10mg/kg) infliximab is an effective and safe adjunctive option for severely ill and disabled patients with central nervous system tuberculosis (CNS TB). This has been planned for evaluation in clinical trials; however, the high cost of infliximab is a major concern in developing countries. Data on low-dose infliximab in CNS TB is sparse. Methods and materials: We conducted a retrospective observational study among CNS TB patients in a quaternary hospital in South India between July 2022 to November 2023. All patients received at least one dose of low-dose (5mg/kg) infliximab in addition to weight-based anti-tuberculous therapy (ATT) and steroids, the current standard of care (SOC) for CNS TB. Disability-free survival (mRS score ≤2) at 3 months was the outcome. Results: Among fifteen CNS TB patients, sixty percent were young men (28.9±9.88, mean ± SD). Twelve had microbiologically confirmed TB. Four of them had drug-resistant TB (2 -MDR, 1-XDR, 1 -Polyresistant). Eight had both brain and spinal cord disease but all had mRS <2. Meningitis, tuberculoma, and hydrocephalus were common radiological findings (60%, 66.67%, and 26.67% respectively). 14 received infliximab for severe paradoxical reaction (PR) with worsening or new tuberculomas with a median duration of 7 (6-11, IQR) months from symptom onset. Two of them had new spinal cord involvement. The median duration of ATT at PR was 5.75 months (IQR, 3-9). The median cumulative steroid dose (prednisolone equivalent) was 765mg (IQR 473 -1341). None had mRS of < 2 at PR. Eleven received at least 3 doses of monthly Infliximab. Eight (53.3%) out of 15 had disability-free survival (mRS of < 2) at 3 months of follow-up. One patient had clinical worsening at 3 months after a single dose of infliximab with extensive endarteritis infarcts suggestive of disease progression. No infliximab-related severe adverse events were noted. Discussion: Our study findings show, that in selected patients with CNS TB low dose of infliximab may improve disability-free survival. The outcome was comparable with the study (53.3%) that used high dose (10 mg/Kg) infliximab in a similar set of patients. Clinical trials can consider using lower doses of infliximab, as they appear to be as efficacious and safe. Conclusion: Low-dose infliximab may be an effective and safe adjunctive treatment for CNS tuberculosis.